ANALYSIS OF THE RELATIONSHIP BETWEEN SUPPLY CHAIN MANAGEMENT AND OUTSOURCING STRATEGIES IN FREIGHT TRANSPORTATION - Skochylias, R. V.; Skochylias, N. V. (The actual problems of regional economy development, 2024)
In the rapidly evolving landscape of freight transportation, the key management systems and outsourcing strategies should be developed for best results, including the whole process optimizations, costs reduction as well as market competitivity improvement. In this paper, the authors seek to explore via in-depth study the subtle intricacies of the link between Supply Chain Management (SCM) decisions and the choice to outsource, in order to unearth unique considerations that will guide important strategic choices in the industry. This research first embodies a systematic literature review and theory and empirical study as well as practical cases from the real world. Finally, the authors present multi-dimensioning implications and practical policy recommendations for supply chain management related to outsourcing initiatives. This research emphasizes the criticality of coordinating the SCM and the strategy for outsourcing to businesses that may be major players in the road and rail freight transportation sector. Strategy mapping generates both operational efficiency and adaptability as well as robustness which becomes a tool to tackle the complications of international supply chains thus allowing the enterprises to respond gracefully to dynamic markets. However, the research also highlights three factors of collaborative partnership, technological integration, and continuous improvement that determine the management and the supply chain outsourcing. Through creation of collaborative governance models, the deployment of advanced tech tools including AI, IoT and blockchain in addition to providing a culture a learning and improvisation, businesses can enhance their supply chain and outperform their competitors in the market space. This research is a contributory factor, revealing the strategic consequences of balancing SCM and outsourcing for the businesses, policymakers, and stakeholders of the industry. It is a point of discussion related to a demand from enterprises for strategic planning processes and governance arrangements to take into account the SCM and outsourcing synergies. Moreover, it emphasizes the fact that administrators should be able to put in place regulations seen to enhance collaborations, discoveries, and funding to the technological projects. Lastly, this research covered deeply all SCM-outsource aspects in this industry freight transportation. Through the extensive observation and the change of the suggested strategies, companies can create new openings for development, innovation, and sustainability in the midst of the world’s supply and logistics environment that is ever changing.